Assessment of mental disorders, lifestyle and quality of life in patients with chronic low back pain - Ovdii Марія; Asanova Азізе (Psychosomatic Medicine and General Practice, 2024)
Background. Chronic low back pain is a global problem today, which poses significant challenges to the health care system around the world. There are trends towards an increase in the number of people with chronic low back pain, especially among the working-age population, which leads to a deterioration in their functioning, psycho emotional state and quality of life. The study of this issue among the working-age population of Ukraine is of considerable interest, since the difficult socio-economic conditions associated with a full-scale war have a direct impact on public health and are a significant trigger for the development of chronic diseases. Objective. To assess mental disorders, lifestyle and quality of life of patients with chronic low back pain to provide relevant interventions for the prevention and treatment of this disease. Materials and methods. A survey of young people of working age 18-40 years was conducted to assess mental disorders, lifestyle and quality of life. The subjects were divided into two groups: a control group of healthy individuals of the same sex and age without low back pain and a comparison group of subjects with chronic low back pain (low back pain lasting >3 months). The subjects completed a questionnaire that included questions about socio-demographic, anthropometric, lifestyle, physical activity data, according to WHO recommendations, SF-36 questionnaire for quality of life, PSS-10 questionnaire for subjective assessment of stress, assessment of depression and anxiety using the Hospital Anxiety and Depression Scale (HADS). Results and discussion. In the group of subjects with chronic low back pain, there were significantly fewer people with normal BMI, 16% were underweight, 34% were overweight, and 6% were obese. The majority of people with chronic low back pain had a sedentary job, including 52% who had a total sitting time of more than 6 hours, 34% of subjects did not have an adequate level of exercise capacity, and 30% had a smoking habit. The average stress level of the control group was 13.4±5.9, which corresponds to a low level of stress, and of the comparison group was 17.06±6.08, which corresponds to an average level of stress (p=0.0029). Among the subjects with chronic low back pain, the majority had a clinical 65% and subclinical anxiety level of 22.5%, as well as a clinical 35% and subclinical depression level of 27.5%. The quality of life was significantly reduced in individuals with chronic low back pain compared to healthy individuals on all scales. On the scales of physical functioning, vitality, pain, and general health, the difference between the groups was significant (p < 0.01). Conclusions. Working-age patients aged 18-40 years with chronic low back pain have a higher level of mental problems, a lower level of quality of life, especially on the scales of the physical component of quality of life, and a higher level of factors that potentiate chronic pain and are related to lifestyle. To improve the results of treatment of patients with chronic low back pain, it is necessary to assess lifestyle, physical activity, mental health and quality of life, and to formulate appropriate recommendations for their correction. Keywords: chronic low back pain, physical activity, quality of life, stress level, chronic pain, depression, anxiety